Thorium- and uranium-azide reductions: a transient dithorium-nitride versus isolable diuranium-nitrides. Issue 13 (28th February 2019) - Du, Jingzhen; King, David M.; Chatelain, Lucile; Lu, Erli; Tuna, Floriana; McInnes, Eric J. L.; Wooles, Ashley J.; Maron, Laurent; Liddle, Stephen T.
Abstract : Evidence for a transient, highly reactive ThNTh nitride is presented, in contrast to uranium analogues that are stable and isolable. Surprisingly, computational studies reveal a σ > π energy ordering for all these bridging nitride bonds, a phenomenon for actinides only observed before in terminal uranium nitrides and uranyl. Abstract : Molecular uranium-nitrides are now well known, but there are no isolable molecular thorium-nitrides outside of cryogenic matrix isolation experiments. We report that treatment of [M(Tren DMBS )(I)] (M = U, 1 ; Th, 2 ; Tren DMBS = N(CH2 CH2 NSiMe2 Bu t )3 3− ) with NaN3 or KN3, respectively, affords very rare examples of actinide molecular square and triangle complexes [M(Tren DMBS )(μ-N3 ) n ] (M = U, n = 4, 3 ; Th, n = 3, 4 ). Chemical reduction of3 produces [U(Tren DMBS )2 (μ-N)][K(THF)6 ] (5 ) and [U(Tren DMBS )2 (μ-N)] (6 ), whereas photolysis produces exclusively6 . Complexes5 and6 can be reversibly inter-converted by oxidation and reduction, respectively, showing that these UNU cores are robust with no evidence for any C–H bond activations being observed. In contrast, reductions of4 in arene or ethereal solvents gives [Th(Tren DMBS )2 (μ-NH)] (7 ) or [Th(Tren DMBS )Th(N[CH2 CH2 NSiMe2 Bu t ]2 CH2 CH2 NSi[μ-CH2 ]MeBu t )(μ-NH)][K(DME)4 ] (8 ), respectively, providing evidence unprecedented outside of matrix isolation for a transient dithorium-nitride. This suggests that thorium-nitrides are intrinsically much more reactive than uranium-nitrides, since they consistently activate C–H bonds to form rare examples of Th–N(H)–Th linkages with alkyl by-products. The conversion here of a bridging thorium(iv )-nitride to imido-alkyl combination by 1, 2-addition parallels the reactivity of transient terminal uranium(iv )-nitrides, but contrasts to terminal uranium(vi )-nitrides that produce alkyl-amides by 1, 1-insertion, suggesting a systematic general pattern of C–H activation chemistry for metal(iv )- vs. metal(vi )-nitrides. Surprisingly, computational studies reveal a σ > π energy ordering for all these bridging nitride bonds, a phenomenon for actinides only observed before in terminal uranium nitrides and uranyl with very short U–N or U–O distances.